Communication! - Aust, Siegfried; Nang Chan Yeema (Minneapolis, MN USA Lerner Publications Company, 1991)
Explains different ways people have communicated throughout history up to present day, including carrier pigeon, smoke signals, and fax.
Keywords: Juvenile Nonfiction